Strain-Induced Band Profile of Stacked InAs/GaAs Quantum Dots - SUKKABOT, Worasak (Walailak Journal of Science and Technology (WJST), 2013)
The strain distribution and band profile in triply stacked InAs/GaAs quantum dots with dot spacing of 0.0 - 6.0 nm was calculated. The continuum elasticity theory for strain distribution and 8-band k.p theory for band structure was used. The use of the k.p method to calculate band structure with and without including the effects of strain is reported. The calculated results show the importance of strain effect on the confinement potential of the band structure for triply stacked InAs/GaAs quantum dots. doi:10.14456/WJST.2014.18